Large Particle Sorting to Isolate Live Parasitic Nematode Eggs. Issue 1 (1st April 2016) - Schmidt, Alfonso; Bouchery, Tiffany; Le Gros, Graham; Price, Kylie M.
Abstract: Traditional jet‐in‐air cell sorters have been designed and optimized to isolate small particles such as mammalian lymphocytes with an average diameter of 10 μm. We discuss the practical considerations of setting up a conventional jet‐in‐air cell sorter, using a 200‐μm nozzle, to isolate the large parasitic nematode eggs of Nippostrongylus brasiliensis, with a maximum size of 60 μm. The eggs were separated based on light scattering properties, no fluorescent dye or molecule was required. © 2016 by John Wiley & Sons, Inc.